Impact of Urinary Tract Infection (UTI) Related Microbial Strains’ Bioactivity Kinetics in Difference Stages for Antimicrobial Susceptibility Testing - Teo, Chee Loong (Journal of Emerging Technologies and Industrial Applications, 2023)
The emergence of UTI problem increasing in worldwide poses diagnostic and therapeutic challenges. Generally, antibacterial related research and product development begin from a laboratory scale, the bioactivity accuracy are crucial before scaling up testing till bioproduct development. In this study, eight strains were studied the impact of bioactivity in different stages with reaction time (0 – 240 minutes) via the Time-kill method. From study showed that all fresh stage strains’ bioactivity are positive and maximum positive specific growth rate (SGR) (min-1) in between 4 – 6 minutes while all aged stage strain’s bioactivity showed negative and maximum negative SGR occurs in between 2 – 30 minutes respectively: Enterococcus faecalis (2.158744057 & -2.649158683), Escherichia coli (2.505317647 & -2.302585093), Proteus vulgaris (2.158744057 & -2.649158683), Klebsiella pneumoniae (2.158744057 & -0.191882091), Candida albicans (2.302585093 & -2.302585093), L. acidophilus (2.302585093 & -2.302585093), L. sakei (2.302585093 & -2.302585093) and L. gassei (1.956011503 & -2.302585093). UTI microbial strains’ bioactivity kinetics were varied depending on stage under an active period with the same cultivation environment and within acceptable bioactivity range only suitable for UTI-related antimicrobial testing.